Nano-Designed Enzyme–Functionalized Hierarchical Metal–Oxide Mesoporous Thin Films: En Route to Versatile Biofuel Cells - Bellino, Martin Gonzalo (2014)
A versatile bioelectronic system is presented, based on Ag nanoparticle assemblies embedded into hierarchically mesoporous titania thin films on which electroactive enzymes are simply immobilized by a fast adsorption process. This strategy enables straightforward, cost effective, high-performance, thin-film enzymatic fuel cell technology with foreseeable applications in self-powered microfluidic and electronic